Mosquitoes In and Around the Home - Faith M. Oi; Renee Anderson (EDIS)
This document is ENY-2004, one of a series of the Department of Entomology and Nematology, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Date first printed: February 2003.